OBSERVATION OF CHILDREN WITH BRONCHIAL ASTHMA IN A POLYCLINIC - Татьяна Николаевна Елкина; Ольга Александровна Грибанова; Наталья Игоревна Пирожкова; Екатерина Александровна Суровикина; Анастасия Сергеевна Кузнецова (The Publishing House Medicine and Enlightenment, 2024)
The aim of the research - assessment of the management of children with bronchial asthma (BA) in the outpatient practice. Materials and methods. The analysis of 112 outpatient records of children aged from 5 to 16 years living in Novosibirsk was carried out. The average age of patients at diagnosis was 5.2 ± 0.4 years. The length of the BA experience at the time of the study averaged 5.9 ± 0.3 years. The characteristics of the course of asthma, the frequency of exacerbations, the need for hospitalization, the adequacy of the basic therapy, the level of achieved control, the atopic status of patients, the presence of comorbid allergic diseases and their impact on the course of asthma, the level of preferential drug provision, the completeness of examinations and studies were analyzed. Results. The most frequently detected was polyvalent sensitization (77.7 %) with a predominance of sensitivity to household (43.8 %) and epidermal (39.3 %) allergens. Significant triggers of exacerbations were also non-immune factors (respiratory infections, physical activity, irritants, pollutants, emotional stress, stressful situations). Almost all patients (95.5%) were diagnosed with comorbid diseases that required therapeutic correction. Allergen-specific immunotherapy was carried out in isolated cases (6.3%), despite the presence of indications. Among patients with mild persistent asthma, only 84.8 % received basic treatment. In patients with moderate disease, basic therapy was prescribed to all, but in 20.5 % the choice of drug was irrational and did not correspond to the severity of the disease. A well-controlled course of disease was recorded in 45.5 %, partially controlled in 27.7 %, uncontrolled in 4.5 %. The medical documentation of 22.3 % of patients did not indicate the level of control, which did not allow determining further management tactics. Monitoring of the course of asthma was insufficient. Conclusion. The reasons for insufficient management of asthma symptoms were lack of control of immune and non-immune triggers, comorbid diseases, low coverage of the allergen-specific immunotherapy, absence or irrational choice of the drugs for basic treatment.